Studer, Helen (audio interview #4 of 4) - Studer, Helen (b. 5/27/1898 - d. 8/00/1981 ); Cleary, Cindy, interviewer
INTERVIEW DESCRIPTION - By the time of the fourth interview, Studer was a bit more comfortable and, ultimately, was pleased that she participated in the project, despite her initial doubts. By the time a transcript was sent to her, her health was failing, and her children read the transcript to her. They were all very pleased with her interview. Unfortunately, portion of this interview suffer from poor audio quality. 10/22/1980